Juridical Analysis of Criminal Liability for the Crime of Impaired Marriage in the Criminal Code (Study Decision Number 17/ Pid.B/ 202/ PN. Blg) - Mohammad Eka Putra; Utary Maharany Barus; Empindonta Ramadhaan Tarigan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
Criminal liability for the crime of obstructing marriage is regulated in article 279 of the Criminal Code which states that anyone who enters into a marriage even though he knows that his existing marriage or marriages are a legal obstacle to that, or whoever enters into a marriage even though he knows that the marriage or marriages of another party become Obstruction to do so is punishable by a maximum imprisonment of five years. There is an example of a case regarding an obstructed marriage as contained in Decision Number 17/Pid.B/2021/PN.Blg, the defendant's actions are regulated and punishable by crime in Article 279 paragraph (1) 1 of the Criminal Code. 1. Declare that the defendant, Estomihi Siahaan, as mentioned above, has been legally and convincingly proven guilty of committing the crime of "entering into a marriage even though knowing that his existing marriage was a legal obstacle to that" as in the first alternative indictment; 2. Sentence the Defendant to prison for 7 (seven) months.